Designing urban agriculture a complete guide to the planning, design, construction, maintenance and management of edible landscapes - Philips, April (Hoboken, New Jersey John Wiley & Sons, 2013)
"This full-color guide offers a complete overview of edible landscapes from the planning, designing, and funding to the management and maintenance of these communal spaces and ecodestinations. Featuring case studies of innovative projects, it offers complete coverage of a dozen typologies including community gardens, CSA farms, edible estates, edible roof gardens, guerilla gardens, vertical wall gardens, and farm-to-table gardens, among others"--Provided by publisher.
"Explains how to design regenerative edible landscapes that benefit both community and ecology Offers complete coverage of management and maintenance issues "--Provided by publisher.
Keywords: Urban agriculture; Edible landscaping; ARCHITECTURE / Landscape